2003
DOI: 10.1507/endocrj.50.355
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Leptin Levels during GnRH Agonist Therapy

Abstract: The purpose of the present study was to investigate changes in serum leptin levels during GnRH agonist therapy. Twenty regularly menstruating women with uterine leiomyomas were enrolled. These subjects were given GnRH agonist (leuprorelin acetate, 3.75 mg) monthly for 4 months. Serum leptin and estradiol (E2) levels were measured at the two time points of day 1 or 2 of the menstrual cycle and the end of GnRH agonist therapy. Weight, total body fat mass, percentage of body fat, and total body lean mass were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…In support of our hypotheses, we observed that ovarian hormone suppression resulted in decreases in FFM and lumbar spine and proximal femur BMD that were prevented by E 2 add-back therapy. Unexpectedly, we did not find an increase in FM in response to GnRH AG +PL, as has been observed by others, 2,3,5,6 but there was an increase in abdominal adiposity as measured by CT.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In support of our hypotheses, we observed that ovarian hormone suppression resulted in decreases in FFM and lumbar spine and proximal femur BMD that were prevented by E 2 add-back therapy. Unexpectedly, we did not find an increase in FM in response to GnRH AG +PL, as has been observed by others, 2,3,5,6 but there was an increase in abdominal adiposity as measured by CT.…”
Section: Discussionsupporting
confidence: 81%
“…2,3,5,6,22 Previous studies included women with uterine leiomyoma, 2,3,5,6,22 or endometriosis. 5 All of these studies found increases in FM and decreases in FFM although not all changes were statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also document a decrease in fat-free mass (FFM), a change seen in some studies. [9][10][11][12] This is also an important observation as FFM determines metabolic rate 13 and, thus, is an important factor in the propensity to gain weight. Because this tissue, which consists primarily of skeletal muscle, diminishes, 13 caloric utilization decreases and adiposity may ensue.…”
mentioning
confidence: 99%